Worldwide Dietary Therapies for Adults With Epilepsy and Other Disorders. (August 2013) - Cervenka, Mackenzie C.; Henry, Bobbie; Nathan, Janak; Wood, Susan; Volek, Jeff S.
During the 3rd International Symposium on Dietary Therapies held in Chicago, Illinois, there was a first-ever, half-day session devoted to the management of adults with epilepsy and other disorders with dietary treatments. Speakers from 3 different continents shared their successes, challenges, and future directions in their management of these patients. Diets used to treat adults included the classic ketogenic diet, the modified Atkins diet, and a low glycemic index treatment. The utility of dietary therapies was demonstrated not only in patients with epilepsy but also patients with propriospinal myoclonus, astrocytoma, type 2 diabetes, obesity, hyperlipidemia, and metabolic disorder. The session provided evidence that dietary therapies are safe and effective in adults.